2021
DOI: 10.3390/ijerph182010729
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intention to Purchase Bottled Water Based on Business Online Strategy in China: The Role of Perceived Risk in the Theory of Planned Behavior

Abstract: With the development of the network economy, especially the promotion and popularization of mobile networks, traditional offline businesses are further integrated with online businesses, promoting the development of business online strategies. However, with the growth of enterprises’ business, their negative externalities on the environment have gradually become prominent, further affecting sustainable consumption. The relationships between businesses, the environment, and consumption have become the focus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…The current study sustains the argument of early researchers who proposed the significance of subject norms in informing consumers’ intention (Mucinhato et al, 2022 ; German et al, 2022 ), confirming the impact of subject norms on consumers’ online takeout purchase behavior. Finally, the development of network technology and the competition between network platforms are making online ordering platforms more and more personalized, entertaining, and easier for consumers to operate, reducing the cost of online ordering while increasing the residual value of consumers (Guo et al, 2021a , 2021b ; Koch et al, 2022 ). Hence, the PBC of consumers is constantly improved, encouraging the purchase of takeout.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study sustains the argument of early researchers who proposed the significance of subject norms in informing consumers’ intention (Mucinhato et al, 2022 ; German et al, 2022 ), confirming the impact of subject norms on consumers’ online takeout purchase behavior. Finally, the development of network technology and the competition between network platforms are making online ordering platforms more and more personalized, entertaining, and easier for consumers to operate, reducing the cost of online ordering while increasing the residual value of consumers (Guo et al, 2021a , 2021b ; Koch et al, 2022 ). Hence, the PBC of consumers is constantly improved, encouraging the purchase of takeout.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tyrväinen and Karjaluoto ( 2022 ) deployed a meta-analysis technique studying 20,538 respondents and then concluded that perceived risks significantly impact consumers’ online grocery purchase intention with attitude as a moderator. Though extant research has shown that perceived convenience, effectiveness, and risks all have significant impacts on consumers’ online purchase intentions, one significant factor that should not be neglected is perceived risk from the outer environment (Afshan and Sharif, 2016 ; Barnes, 2019 ; Guo et al, 2021a , 2021b ). In fact, it is likely that when consumers understand that the packaging of online takeout may be harmful to their health and the environment, their attitude, subjective norms, and PBC pertaining to takeout will significantly reduce as well.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patak et al ( 2021 ) put forward the concept of consumers' green purchase intention and pointed out that environmental concern, green lifestyle, and product knowledge are the main influencing factors. Similarly, Guo et al ( 2021 ) put forward the concept of sustainable consumption intention. Thus, COVID-19 has profoundly changed the underlying factors of consumer buying behavior (Valaskova et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, el tiempo y el esfuerzo que las personas deben dedicar al aprendizaje del uso de Internet. Por su parte, Kim et al, (2021)innovativeness toward online buying, involvement with the Internet, and frequency of Internet use; Guo et al, (2021); Alia y Naushadb, (2021) y Ofori y Nimo, (2019) en los modelos planteados resaltan la aplicación, el efecto directo y positivo de la exposición y experiencia con el internet en la decisión de compra.…”
Section: Modelos De Comportamiento Del Consumidorunclassified